Patient reported outcome and quality of life measured by a simple questionnaire in patients with symptomatic benign prostate hyperplasia treated by holmium laser enucleation of the prostate (HoLEP) - Schumacher, Stephanie; Marghawal, David; Brunken, Claus; Herzberg, Jonas (Frontiers in Surgery, 2024)
Introduction: Holmium Laser Enucleation of the Prostate (HoLEP) is established as an effective transurethral treatment option for LUTS due to BPH with improved postoperative outcome. The aim of this study was to evaluate the medium-term results by patient reported outcome measurement and to detect potential risk factors for postoperative complications or impaired outcome. Methods: We performed a retrospective single-center cohort study including all patients undergoing HoLEP in the study center between April 2019 and December 2021. Therefore, perioperative parameters and postoperative outcome was documented and all patients were asked for their outcome (PROM), complications, IPSS, QoL and changes in sexual and continence function by a questionnaire at a single time point. Results: In the study period, a total of 541 patients with a mean age of 72.5 ± 8.4 years were treated by HoLEP in the study center. 71.7% of the questionnaires were returned after a mean observation period of 14.9 ± 6.3 month. 91% of the patients reported to the single-timepoint questionnaire reporting a good satisfaction with the procedure and a low postoperative complication rate. The international prostate symptom score could be reduced significantly to 6.2 ± 5.7 (preoperative 19.0±7.2; p<0.001). Patients with an ASA score ≥3, prostate volume > 80ml, medication with platelet inhibitors or DOAK or preoperative need of an indwelling catheter didn’t show an increased complication rate. Conclusion: The overall satisfaction with the procedure and its results are high. We could not identify any independent risk factors for postoperative complications after HoLEP. The used questionnaire is a simple tool for postoperative patient reported outcome measurement with a good correlation to clinical parameters.